Neovascularisation and pain in jumper's knee: a prospective clinical and sonographic study in elite junior volleyball players. Issue 7 (23rd June 2005) - Gisslén, K; Alfredson, H
Abstract : Background: The nature of tendon neovascularisation associated with pain over time has not been studied. Objective: To prospectively study the patellar tendons in elite junior volleyball players. Methods: The patellar tendons in all students at the Swedish National Centre for high school volleyball were evaluated clinically and by ultrasonography (US) and Power Doppler (PD) sonography. Results: Altogether 120 patellar tendons were followed for 7 months. At inclusion, jumper's knee was diagnosed clinically in 17 patellar tendons. There were structural changes on US in 14 tendons, in 13 of which PD sonography showed neovascularisation. There were 70 clinically normal tendons with normal US and PD sonography, 24 clinically normal tendons with abnormal US but normal PD sonography, and nine clinically normal tendons with abnormal US and neovascularisation on PD sonography. At 7 month follow up, jumper's knee was diagnosed clinically and by US in 19 patellar tendons, in 17 of which there was neovascularisation. Three of nine clinically normal tendons with structural changes and neovascularisation at inclusion developed jumper's knee. Two of 24 tendons clinically normal at inclusion, with abnormal US but normal PD sonography, developed jumper's knee with abnormal US and neovascularisation on PD sonography. A total of 20 clinically normal tendons with normal US and PD sonography at inclusion developed structural tendon changes and 12 of these also developed neovascularisation. Conclusions: The clinical diagnosis of jumper's knee is most often associated with neovascularisation in the area with structural tendon changes. The finding of neovessels might indicate a deterioration of the condition.